Concentration of Wealth and Economic Inequality from the Perspective of Maqāṣid al-Syarī‘ah: A Case Study of Sidrap Regency - Nurul Asia; Zainal Said; Hannani Hannani (Borneo Islamic Finance and Economics Journal, 2026)
This study aims to analyze the concentration of wealth and the inequality of economic distribution in Sidenreng Rappang Regency and examine the role of sharia economic principles in realizing economic justice based on the maqāṣid al-syarī‘ah framework. This study uses a qualitative method with a field research approach. Data were obtained through in-depth interviews with seven informants consisting of academics, community leaders, business actors, and zakat institution managers, supported by observation and documentation. Data analysis was conducted using the interactive model of Miles and Huberman which includes data reduction, data presentation, and conclusion drawing/verification. The results of the study indicate that the inequality of economic distribution in Sidenreng Rappang Regency is influenced by the concentration of capital ownership, limited economic access for small communities, weak distribution of business opportunities, and the dominance of certain groups in controlling economic resources. These conditions cause the distribution of wealth to not be fair and equitableFrom the perspective of the maqāṣid al-syarī‘ah (Islamic principles), this phenomenon does not fully reflect the principles of distributive justice and social welfare because there are still obstacles in fulfilling the economic welfare of society in an inclusive manner. This study also found that Islamic economic instruments, such as zakat, infaq, sadaqah, waqf, and strengthening Islamic micro-enterprises, have strategic potential in reducing economic inequality. However, their implementation still faces various obstacles, particularly the dominance of consumptive distribution patterns and the suboptimal empowerment of the productive economy. Theoretically, this study expands the study of Islamic economics by placing the maqāṣid al-syarī‘ah as an analytical framework to evaluate the phenomenon of wealth concentration and economic inequality at the local level. Unlike previous studies that generally focused on the effectiveness of zakat, infaq, sadaqah, and waqf instruments, this study shows that wealth distribution also needs to be analyzed from the aspect of the structure of control of economic resources and the level of achievement of distributive justice in society. The novelty of this research lies in the integration of the perspectives of economic dominance and maqāṣid al-syarī‘ah in explaining the relationship between wealth concentration, community economic access, and the achievement of social welfare in the local economic context of Sidenreng Rappang Regency. Keywords: Distribution of wealth, sharia economics, Sidenreng Rappang district, economic inequality, maqāṣid al-syarī‘ah.